Educação à distância e sua comparação com o método tradicional de ensino : um estudo experimental prospectivo randomizado - Aragão, João Fernandes Britto (2014)
Teaching topics related to handling water and electrolytes are always a challenge for the medical educator. Faced with the complex area is essential to the physical presence of a teacher in the classroom, or can the student educate themselves with the aid of e-Learning? For the purpose of responding to this question, 62 volunteer undergraduate medical students in the State of Sergipe, Brazil, without prior experience in the specific approach of clinical and therapeutic aspects related to electrolyte balance, were submitted, after random assignment in cascade in accordance with their year of entry to the University and the learning method adopted at the institution (conventional or active methodology), a longitudinal analytical experimental study. The students were randomly assigned to two groups (classroom and distance) receiving lessons for the management of water and electrolytes. Evaluative evidence, with the same content, were applied to the two groupings, at two distinct times: for assessment of prior knowledge (pre-test) and assimilated knowledge (post-test). This defined the gain of learning as well as the difference between the averages of the pre-test and post-test. The data were submitted to descriptive and inferential analysis and significance level for rejection of the null hypothesis which was 0.05. On the basis of the evaluations were calculated measures of central tendency, dispersion and confidence interval. Gains in learning were evaluated using the paired t-test. The groups were compared by means of Student´s t test for independent samples. The statistical analysis showed no significant difference in the learning gain in the comparison between the groups (p= 0.58), indicating that the distance education is as good as the classroom in teaching Hydroelectrolytic Balance and its disorders.